2014
DOI: 10.1016/j.cellimm.2014.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids regulate natural killer cell function epigenetically

Abstract: Although glucocorticoids are well known for their capacity to suppress the immune response, glucocorticoids can also promote immune responsiveness. It was the purpose of this investigation to evaluate the molecular basis for this apparent dichotomous immunologic effect. Glucocorticoid treatment of natural killer cells (NK) was shown to reduce NK cell cytolytic activity by reduction of histone promoter acetylation for perforin and granzyme B, which corresponded with reduced mRNA and protein for each. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 91 publications
(112 reference statements)
1
57
0
1
Order By: Relevance
“…As epigenetic regulation of other pro-inflammatory genes such as TNF-α and IL-6 have been demonstrated in other immune cell types such as natural killer cells and peripheral monocytes/macrophages (Eddy, et al, 2014, Sullivan, et al, 2007), it will be pertinent to explore regulation by DNA methylation and other epigenetic modifications in microglia, as well as other signature genes relevant to aging such as those recently found in the microglial sensome (Hickman, et al, 2013) or other recent transcriptomic studies (Holtman, et al, 2015, Orre, et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…As epigenetic regulation of other pro-inflammatory genes such as TNF-α and IL-6 have been demonstrated in other immune cell types such as natural killer cells and peripheral monocytes/macrophages (Eddy, et al, 2014, Sullivan, et al, 2007), it will be pertinent to explore regulation by DNA methylation and other epigenetic modifications in microglia, as well as other signature genes relevant to aging such as those recently found in the microglial sensome (Hickman, et al, 2013) or other recent transcriptomic studies (Holtman, et al, 2015, Orre, et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…119 Several authors demonstrated that GCs epigenetically reduce NK cytolytic activity, while at the same time prime NK cells for proinflammatory cytokine production. 120 Thus, relationship between steroid treatment and innate immune regulation is still under investigation (Table I, Fig. 2).…”
Section: Therapeutical Insights and Future Directionsmentioning
confidence: 99%
“…GC treatment was also shown to enhance activity of histone deacetylases (HDACs) 7, 9, 10, and 11 of mice splenic memory T cells [41]. However, a recent study showed that chronic GC treatment of natural killer cells (NK) can reduce NK cell granzyme B productions by reduction of histone promoter H4K8Ac as well as H3K9Ac while increasing IFN-γ and IL-6 production by increasing H4K8Ac/H3K27Ac as well as H3K4me3 in regulatory regions at the same time [42]. This dichotomous effect of GC on immune function seems to be dose- and time-dependent [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study showed that chronic GC treatment of natural killer cells (NK) can reduce NK cell granzyme B productions by reduction of histone promoter H4K8Ac as well as H3K9Ac while increasing IFN-γ and IL-6 production by increasing H4K8Ac/H3K27Ac as well as H3K4me3 in regulatory regions at the same time [42]. This dichotomous effect of GC on immune function seems to be dose- and time-dependent [42]. Thus deacetylation cannot totally explain the effects of GC treatment on histone modification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation